ROLE OF GUIDANCE AND COUNSELING IN COMBATING THE INCIDENCE OF HEALTH COMPROMISING BEHAVIORS AMONG UNDERGRADUATES IN ENUGU STATE, NIGERIA - Onah, Paschal C. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
The current study investigated the role of guidance and counseling in controlling health-compromising behaviors in a sample of undergraduates in Enugu state, Nigeria. A quasi-experimental post-test-only nonequivalent control group design was used to study the effects of guidance and counseling on measures of health risk behaviors. Seventy-six participants were assigned to groups, with group A representing the experimental group and group B as the control group. An independent-samples t-test was conducted to compare guidance and counseling and non-guidance and counseling conditions. There was a significant difference in the score for G&C (M= 4.3, SD = 1.6) and no G&C (M = 3.2, SD = 0.33) groups; t (74) = 3.89, p = 0.020. These results suggest that G&C does affect health-compromising behavior. The result has implications for school counseling and risky behavior management. The study recommended that counseling psychologists and school counselors be well trained in the use of CBT in addressing risky behaviors, especially among adolescents.